KONTROL LAMPU RUANG LAB MENGGUNAKAN PERINTAH SUARA BERBASIS ARDUINO UNO - Dede Supiyan; Zainudin (Journal of Research and Publication Innovation, 2025)
Utilizing the time needed in a work process, the speed of data transfer is direct human work, so IoT (Internet of Things) is currently the answer to all needs that replace direct physical functions, through data transfer using internet network media which is assisted by a microcontroller device to implement many things in everyday life, both in the industrial world, laboratories, agriculture, health and household needs. This Internet of Things (IoT) based lighting control system application uses an Arduino Uno as a microcontroller and an Android application as a control tool. This system is used to control the lights on or off. Apart from that, the design of this system also uses a relay which is used to connect the light to the system. From the results of testing and analysis, the control of electronic equipment in this light control system operates according to the commands given. As long as the system is connected to the internet network stably, there will be no problems with the IoT (Internet of Things) based light control system using Arduino Uno with voice commands using the Bluetooth voice application.